Molecules and Medicine - E J Corey (John Wiley & Sons, 2007)
Molecules and Medicine provides, for the first time ever, a completely integrated look at chemistry, biology, drug discovery, and medicine. It delves into the discovery, application, and mode of action of more than one hundred of the most significant molecules in use in modern medicine. Opening sections of the book provide a unique, clear, and concise introduction, which enables readers to understand chemical formulas.